Vitamin E: Emerging aspects and new directions - KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE INC, 2017)
The discovery of vitamin E will have its 100th anniversary in 2022, but we still have more questions than answers regarding the biological functions and the essentiality of vitamin E for human health. Discovered as a factor essential for rat fertility and soon after characterized for its properties of fat-soluble antioxidant, vitamin E was identified to have signaling and gene regulation effects in the 1980s. In the same years the cytochrome P450 dependent metabolism of vitamin E was characterized and a first series of studies on short-chain carboxyethyl metabolites in the 1990s paved the way to the hypothesis of a biological role for this metabolism alternative to vitamin E catabolism. In the last decade other physiological metabolites of vitamin E have been identified, such as alpha-tocopheryl phosphate and the long-chain metabolites formed by the w-hydroxylase activity of cytochrome P-450. Recent findings are consistent with gene regulation and homeostatic roles of these metabolites in different experimental models, such as inflammatory, neuronal and hepatic cells, and in vivo in animal models of acute inflammation. Molecular mechanisms underlying these responses are under investigation in several laboratories and side-glances to research on other fat soluble vitamins may help to move faster in this direction. Other emerging aspects presented in this review paper include novel insights on the mechanisms of reduction of the cardiovascular risk, immunomodulation and antiallergic effects, neuroprotection properties in models of glutamate excitotoxicity and spino-cerebellar damage, hepatoprotection and prevention of liver toxicity by different causes and even therapeutic applications in non-alcoholic steatohepatitis. We here discuss these topics with the aim of stimulating the interest of the scientific community and further research activities that may help to celebrate this anniversary of vitamin E with an in-depth knowledge of its action as vitamin.
Keywords: Vitamin E; Tocopherols; Tocotrienols; Cytochrome P-450; Antioxidants; Long-chain metabolites, Tocopheryl phosphate; Nutrition; NASH; PROTEIN-KINASE-C; ALPHA-TOCOPHERYL-PHOSPHATE; FATTY LIVER-DISEASE; DENDRITIC CELL-DIFFERENTIATION; CD34(+) HEMATOPOIETIC PROGENITORS; SCAVENGER RECEPTOR EXPRESSION; COLONY-STIMULATING FACTOR; SMOOTH-MUSCLE-CELLS; GAMMA-TOCOPHEROL; GENE-EXPRESSION